PERANAN AUTOPSI FORENSIK DAN KORELASINYA DENGAN KASUS KEMATIAN TIDAK WAJAR - Widowati Widowati; Y. A. Triana Ohoiwutun; Fiska Maulidian Nugroho; Samsudi Samsudi; Godeliva Ayudyana Suyudi (Refleksi Hukum: Jurnal Ilmu Hukum, 2021)
A forensic autopsy aims to find a definite cause of a person’s death by revealing the material truth scientifically from the beginning of case investigation to its trial examination. In judicial practices, a forensic autopsy is considered a pivotal tool in proving material criminal acts. However, KUHP Article 222 and KUHAP Article 133-134 regulate forensic autopsy procedures requiring prior notification to the victim's family. These provisions have hindered law enforcement in certain unnatural death cases. Therefore, this article encourages forensic autopsy implementation must not wait for a family consent of a victim for the sake of fair legal certainty to the victims, perpetrators, and also for society.